2011
DOI: 10.1142/s136391961100343x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Customers' Resistance to Industrial Service Innovations

Abstract: This paper examines the reasons for corporate customers' resistance to adopt industrial service innovations provided by their supplier companies. It is based on work with nine Finnish suppliers of industrial services and their potential customers. We view organizations as networks of individual adopters. We find that organizational sentiment towards adopting an innovation is often ambivalent and that resisting views reveal important drawbacks of an innovation that need to be addressed. The results clarify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Finally, FLE co-creation favors FLEs' adoption of the service innovation, leading to a much stronger commitment to the service provision process (Korhonen and Kaarela 2011). In sum, FLE co-creation is expected to have a favorable impact on customer-related performance indicators such as customer satisfaction, loyalty, and other perceived benefits, which are designated in this research as customer outcomes.…”
Section: Fle Co-creation and Customer Outcomesmentioning
confidence: 89%
See 3 more Smart Citations
“…Finally, FLE co-creation favors FLEs' adoption of the service innovation, leading to a much stronger commitment to the service provision process (Korhonen and Kaarela 2011). In sum, FLE co-creation is expected to have a favorable impact on customer-related performance indicators such as customer satisfaction, loyalty, and other perceived benefits, which are designated in this research as customer outcomes.…”
Section: Fle Co-creation and Customer Outcomesmentioning
confidence: 89%
“…However, in analyzing the effect of FLE co-creation on customer outcomes, the expected causal relationship was not significant (H3: path coefficient=0.079; tstatistic=1.027). This was so even though the literature states that FLE co-creation allows incorporating into the NSDP valuable market information, which has a positive effect on the service innovation performance among customers (Cadwallader et al 2010;Korhonen and Kaarela 2011). In the resources route, H4 was confirmed; thus, FLE outcomes positively influence customer outcomes (path coefficient= 0.402; t-statistic=4.355; p<0.01).…”
Section: Structural Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…That this remains a challenge is evidenced by a study, reported as recently as 2011, on customers' information needs during innovation adoption (Talke & Colarelli O'Connor [19]). Similar resistance to technology innovations led to recent research in the industrial project [13] and industrial service [12] domains. A discontinuous (radically innovative) product is less likely to succeed because of insufficient understanding of the complex qualitative reasoning that the customer tends to pursue in arriving at the decision to procure it.…”
Section: Introductionmentioning
confidence: 81%